Anti-biofilm effectiveness of protocols for cleaning complete dentures in hospitalized patients: a randomized controlled trial - Anna Clara Gurgel GOMES; Janaina Gomes MACIEL; Amanda Aparecida Maia Neves GARCIA; Letycia Accioly Simões COELHO; Giulia Murcia RODRIGUES; Vinicius Carvalho PORTO; Grigorios POLYZOIS; Marlise Inêz KLEIN; Simone SOARES; Vanessa Migliorini URBAN; Karin Hermana NEPPELENBROEK (University of São Paulo, 2024)
Abstract Denture biofilm acts as a potential reservoir for respiratory pathogens, considerably increasing the risk of lung infections, specifically aspiration pneumonia, mainly 48h after hospital admission. The establishment of a straightforward, affordable, and applicable hygiene protocol in a hospital environment for the effective control of denture biofilm can be particularly useful to prevent respiratory infections or reduce the course of established lung disease. Objectives To evaluate the anti-biofilm effectiveness of denture cleaning protocols in hospitalized patients. Methodology The maxillary complete dentures (MCDs) of 340 hospitalized participants were randomly cleaned once using one of the following 17 protocols (n=20): brushing with distilled water, toothpaste, or neutral liquid soap (controls); immersion in chemical solutions (1% sodium hypochlorite, alkaline peroxide, 0.12% or 2% chlorhexidine digluconate), or microwave irradiation (650 W for 3 min) combined or not with brushing. Before and after the application of the protocols, the biofilm of the intaglio surface of the MCDs was evaluated using two methods: denture biofilm coverage area (%) and microbiological quantitative cultures on blood agar and Sabouraud Dextrose Agar (CFU/mL). Data were subjected to the Wilcoxon and Kruskal-Wallis tests (α=0.05). Results All 17 protocols significantly reduced the percentage area of denture biofilm and microbial and fungal load (P<0.05). The highest percentage reductions in the area of denture biofilm were observed for 1% hypochlorite solution with or without brushing and for 2% chlorhexidine solution and microwave irradiation only in association with brushing (P<0.05). The greatest reductions in microbial and fungal load were found for the groups that used solutions of 2% chlorhexidine and 1% hypochlorite and microwave irradiation, regardless of the association with brushing (P<0.05). Conclusions A single immersion for 10 min in 1% sodium hypochlorite, even in the absence of brushing, proved to be a straightforward, rapid, low-cost, and effective protocol for cleaning the dentures of hospitalized patients.